The hidden/ hard to reach men who have sex with men (MSM)—Results from the qualitative study in India - Seema Sahay; Dhammasagar Ujagare; Girish Rahane; Tuman Lal Katendra; Amarendra Mahapatra; Shivendra Kumar Singh; Sanjeev Kumar; Chinmoyee Das; Bhawani Singh Kushwaha; Vinita Verma; Rajiv Ranjan Tiwari; Nupur Mahajan; et al. (PLoS ONE, 2026)
Background To ensure a substantial impact and prevent the resurgence of the epidemic, the HIV programmes should effectively reach hidden key populations (KPs). A qualitative study was conducted to understand hidden men who have sex with men (MSM), and their needs and identify outreach strategies for those who were still unreached. Methods Between 17 March 2019 and 26 July 2019, 42 In-depth Interviews (IDIs), 40 Key Informant Interviews (KIIs), and 16 Focus Group Discussions (FGDs) were conducted covering 170 participants across four states of India. Data were audio recorded, transcribed, translated and analyzed using NVivo software employing a grounded theory approach. Results A diverse spectrum of unreached men were reportedly practicing same-sex behaviors and new hidden MSM categories have been identified. These hidden MSM demonstrated denial, lack of awareness, and a history of forced sexual experiences. Being elusive, hence no access to healthcare services and education resulted in condom-less sex. The very young adolescent MSM were unaware of the risks and perceived risky practices as the norm. Both at urban and rural settings, MSM respondents shared about sexual abuse by a male while studying in 2 nd standard to 6 th standard. The ‘sugar daddies/ older MSM’ who were >50 years old get disengage from the programme, preferentially practice high-risk behaviors, abusing young boys and men who fall prey for money or easy fun. Peers were the most acceptable persons to reach ‘hidden’ MSM. Conclusion A peer-driven approach based on the inbuilt trust of the community and leveraging networks might be a vital outreach strategy to engage this elusive, vulnerable hidden MSM. The vulnerability of young boys and men calls for an urgent need for fostering safer environment for minor male children in the context of this study and strong integration of POCSO Act in the programme. Additionally, there is an urgent need to revisit strategies for engaging middle-aged MSM, the ‘sugar daddies’ or ‘uncles’ in preventing spread of HIV. Policymakers and educational institutions may prioritize comprehensive sex and sexuality education to challenge and transform prevailing social norms affecting young boys in India. It is important for parents and carers to be alert about how these abuse happen, and how to help prevent it.